(untitled) (Research, Society and Development, 2024)
The Pouca Saúde River communicates with the Porto de Santos Estuary, in the Porto neighborhood in Guarujá. Along the river there are many stilt houses releasing sewage and domestic waste. The objective was to verify whether semi-domiciled dogs from the Pouca Saúde River region can be biomarkers of environmental contamination. Semi-domiciled dogs that constantly roamed the banks of the Pouca Saúde River were included. The dogs were subjected to clinical evaluation, to check for possible injuries to paws and limbs, and kidney and liver function was checked and Antimony, Cadmium, Lead, Chromium, Mercury, Nickel and Zinc were measured. The dogs received multiple and anti-rabies vaccines, an identification collar and an antiparasitic collar. Blood analysis from 30 dogs (50% females) with an average age of 4.1 years, identified high concentrations of the metal Zinc in 27 individuals (90%) (Zn = 3.37 mg/kg ±0.71), which was also found in high concentrations in the sediments of the Pouca Saúde River (Zn = 193.9 mg/kg). Four dogs (13.3%) showed a mild to moderate increase in the number of reticulocytes in plasma (10³/mm³). These animals showed a significant reduction in the concentration of MCV (p<0.05), monocytes (p<0.03) and creatinine (p<0.003) compared to animals that did not present these cells. There was a moderate positive linear association in relation to total Zinc concentration and number of red blood cells, hemoglobin concentration and hematocrit in plasma (p<0.05). Semi-domiciliated dogs from Sítio Conceiçãozinha, Guarujá, São Paulo, can be considered as biomarkers/sentinels of environmental contamination for toxic metals.